Post-TPP trade policy options for Asean and its dialogue partners : “preference ordering” using CGE analysis - Ji, Xianbai (2019)
Trump’s withdrawal from the Trans-Pacific Partnership (TPP) and his “America First” trade agenda ignite a second round of interest in mega-free trade agreements in the Asia-Pacific. Countries are evaluating alternative trade policy actions in a post-TPP era. Using national real GDP gains estimated by a modified GTAP model to construct “preference ordering” for 10 Association of Southeast Asian Nations members and their six regional dialogue partners, this paper comes up with several policy-oriented findings. First, when multilateral agreements are not possible, countries are better off with a regional trading agreement than without one. Second, the Regional Comprehensive Economic Partnership is likely to have higher beneficial impacts than the Comprehensive and Progressive Agreement for Trans-Pacific Partnership. Third, for dual-track countries, implementing both agreements is better than each separately. Fourth, impacts of open regionalism are likely to be higher than those of a closed and reciprocal one. Going forward, this paper argues that countries should adopt a “multi-track, multi-stage” approach to trade policy.